ANALISIS PENGENDALIAN INTERN PEMBERIAN KREDIT TANPA AGUNAN (KTA) DALAM HUBUNGANNYA DENGAN PENETAPAN RESIKO KREDIT PADA PT. BANK MANDIRI (Persero) Tbk CABANG SUDIRMAN PALEMBANG - Lili Syafitri (JURNAL KOMPETITIF, 2013)
This research aims to analyze the internal control in order to reduce the level of bad debts on delivery Credit Unsecured PT. Bank Mandiri (Persero) Tbk Branch Sudirman Palembang, with the formulation of the problem of how the internal control provision Loan (KTA) at PT. Bank Mandiri (Persero) Tbk Sudirman Palembang Branch in relation to credit risk.To conduct research in order to get the necessary data in the discussion, the authors used a qualitative descriptive analysis method, which provides an explanation of the company overview, the separation of the operational and control procedures that exist.The analysis conducted in this study was to assess the effectiveness of internal control provision Loan (KTA) at PT. Bank Mandiri (Persero) Tbk Sudirman Palembang Branch in relation to credit risk.Based on the results of research and analysis has been done, it was concluded that surveillance conducted by Officer and Manager PT. Bank Mandiri (persro) Tbk Branch Sudirman Palembang in granting Loan (KTA) either direct field supervision or administrative supervision is appropriate / effective. Keywords: Internal Controls, Loan and Credit Risk